A novel approach to methoxy polyethylene glycol-grafted sulfonated poly(maleic anhydride-alt-styrene) as superplasticizers in cement pastes. (17th March 2023) - Jiang, Bingzheng; Chen, Dong; Wang, Li; Yang, Wantai
Graphical abstract: Highlights: Gas-solid heterogeneous sulfonation reaction and esterification reaction were adopted to synthesize superplasticizers. The relationship between sulfonation degree, Mn of mPEG, grafting density and fluidity was investigated systematically. Adsorption kinetics tests unveiled that the adsorption capacity attenuated due to excessive grafting density. Superplasticizers performed best dispersing ability with grafting density 2/3 and molecular weight of mPEG 4000 g/mol. Abstract: In this research, a novel method was developed to synthesize methoxy polyethylene glycol-grafted sulfonated poly(maleic anhydride- alt -styrene) (SPMS-g-mPEG) as cement superplasticizers. The method includes three main steps: 1) self-stabilized precipitation polymerization (2SP) of styrene and maleic anhydride for PMS microspheres; 2) gas-solid heterogeneous sulfonation reaction (GSR) of gaseous SO3 with PMS microspheres; 3) intramolecular sulfonic acid-catalyzed esterification reaction of mPEG with sulfonated PMS (SPMS). GSR can achieve uniform sulfonation of PMS microspheres, while overcoming the inherent drawbacks of the traditional homogeneous solution sulfonation process. SPMS and SPMS-g-mPEG with different structural parameters and uniform structure were successfully prepared and their effects on the fluidity and fluidity retention of cement pastes were systematically compared. For the samples demonstrating the best dispersing ability, the hydration heat and setting time of cement pastes, adsorption kinetics and compressive strength of mortar samples were determined further. Our work provides an innovative and effective approach to superplasticizers with outstanding properties and its uniform structure facilitates the investigation on the relationship between structure and properties.